Total extract of Abelmoschus manihot L. alleviates uric acid-induced renal tubular epithelial injury via inhibition of caspase-8/caspase-3/NLRP3/GSDME signaling - Ding, Zhihui; Zhao, Jing; Wang, Xufang; Li, Wei; Chen, Chong; Yong, Chen; Zhu, Yiye; Tian, Fang; Liu, Li; Yu, Manshu; Zhou, Enchao; Gu, Liubao; et al. (Frontiers in Pharmacology, 2022)
Purpose: The incidence of uric acid (UA)-induced kidney injury is increasing owing to the high incidence of hyperuricemia in recent years. The flower of Abelmoschus manihot (Linneus) Medik is a traditional Chinese medicinal herb widely used in the treatment of some kidney diseases. In our previous study, we reported that the total extract of A. manihot L. flower (TEA) attenuated adriamycin-induced renal tubular cell injury. In this study, we aimed to evaluate the role of TEA in UA-induced tubular cell injury. Methods: Normal rat proximal epithelial NRK-52E cells were incubated with UA to mimic hyperuricemia conditions. The role of TEA in the renal tubular cells was also assessed. The cellular morphology was observed using phase-contrast microscopy, and cell viability was analyzed using the Cell Counting kit-8. Living and dead cells were stained using a Calcein-AM/PI double stain kit. The release of lactate dehydrogenase (LDH) was analyzed by LDH cytotoxicity Assay Kit. The expression of target proteins was analyzed using western blot analysis. Results: UA triggered NRK-52E cell injury, as evidenced by morphological changes, detachment of cells from the bottom, cell swelling, large bubbles blowing from cell membrane and loss of cell viability. UA increased release of LDH. UA induced the expression of p-ERK1/2 and the subsequent activation of caspase-8, caspase-3, and NLRP3 inflammasomes. Pyroptosis was elicited by UA after gasdermin E N-terminal (GSDME-NT) was cleaved from gasdermin E (GSDME). Z-DEVD-FMK, a caspase-3 inhibitor, suppressed the expression of both NLRP3 and GSDME-NT, but not that of caspase-8. INF39, an NLRP3 inhibitor, altered the expression of GSDME-NT expression, but not that caspase-3 and caspase-8. TEA alleviated UA-induced cell injury by suppressing ERK1/2/caspase-8/caspase-3/NLRP3/GSDME signaling. Conclusion: GSDME-mediated pyroptosis was involved in UA-induced renal tubular cell injury. This is the first study to report that TEA protects renal tubular epithelial cells against UA by inhibiting the ERK/1/2/caspase-8/caspase-3/NLRP3/GSDME pathway.